2020
DOI: 10.1111/inr.12607
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ health beliefs about paper face masks in Japan, Australia and China: a qualitative descriptive study

Abstract: Aim To explore the health beliefs of clinical and academic nurses from Japan, Australia and China regarding wearing paper masks to protect themselves and others, and to identify differences in participants' health beliefs regarding masks. Background The correct use of face masks and consensus among health professionals across the globe is essential for containing pandemics, and nurses need to act according to policy to protect themselves, educate the public and preserve resources for frontline health workers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…It is a systematic and rigorous method widely used in qualitative research to extract themes and subthemes (underlying factors) from interviews e.g. [ 20 , 27 , 34 , 35 ]. Hence, this study employed content analysis to analyse the results of the interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a systematic and rigorous method widely used in qualitative research to extract themes and subthemes (underlying factors) from interviews e.g. [ 20 , 27 , 34 , 35 ]. Hence, this study employed content analysis to analyse the results of the interviews.…”
Section: Methodsmentioning
confidence: 99%
“…For qualitative research, Omura, Stone, Petrini and Cao [ 27 ] conducted a qualitative descriptive study to find out how clinical and academic nurses in Japan, Australia, and China feel about wearing face masks to protect themselves and others and to see whether there are any variations in their attitudes toward wearing masks. They found that nurses from various work contexts, nations, and areas of practice hold a variety of personal and professional health attitudes concerning mask use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These strategies can be difficult and time consuming to adhere to in practice. Previous studies (Atay & Cura, 2020;Houghton et al, 2020;Omura et al,2020) show barriers and facilitators among nurses for the correct use of PPE, and adherence to safety protocols. Multiple barriers exist such as shortage of PPE, lack of training, failure to update safety protocols, lack of staffing, physical injury from PPE, lack of trust among superiors, beliefs and stereotypes.…”
Section: Introductionmentioning
confidence: 98%
“…More specifically, the idea of content analysis is to count the similar keywords or content of the collected data, extract the point of view, and label it [14,23]. Content analysis is a systematic and rigorous approach widely used in qualitative research to elicit themes and subthemes (underlying factors) from qualitative opinions [e.g., 3,26,34,52,56]. Hence, this study adopted the content analysis method to analyse students' qualitative opinions.…”
Section: Discussionmentioning
confidence: 99%